2022
DOI: 10.1007/s43440-021-00344-x
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on the applications of furin inhibitors for the treatment of SARS-CoV-2

Abstract: Currently, the world is facing a pandemic of the new coronavirus SARS-CoV-2 that causes COVID-19. Identifying key targets in the viral infection lifecycle is urgently needed for designing therapeutic strategies to combat the virus. Furin is a subtilisin-like proprotein convertase with diverse cellular functions. Emerging evidence suggests that furin plays a critical role in the activation and/or infectivity of SARS-CoV-2. In this perspective, we discuss the potential role of furin in the entry SARS-CoV-2 into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Several compounds with potency inhibit human furin, e.g., decanoyl-Arg-Val-Lys-Arg-chloromethylketone, α1-antitrypsin Portland or succinoyl esters of andrographolide isolated from the herbaceous plant Andrographis paniculate (Burm.f.) Nees [ 74 ]. As evidenced, furin inhibitor decanoyl-RVKR-CMK has been demonstrated to inhibit the processing of SARS-CoV-2 successfully.…”
Section: Pharmaceutical Targets Of Sars-cov-2mentioning
confidence: 99%
“…Several compounds with potency inhibit human furin, e.g., decanoyl-Arg-Val-Lys-Arg-chloromethylketone, α1-antitrypsin Portland or succinoyl esters of andrographolide isolated from the herbaceous plant Andrographis paniculate (Burm.f.) Nees [ 74 ]. As evidenced, furin inhibitor decanoyl-RVKR-CMK has been demonstrated to inhibit the processing of SARS-CoV-2 successfully.…”
Section: Pharmaceutical Targets Of Sars-cov-2mentioning
confidence: 99%
“… 67 , 68 Therefore, inhibition of Furin may potentially suppress virus infection by twofold, via restraining viral entry and enhancing the immune response for viral clearance. 33 …”
Section: Potential Pathogenic Targets Of Sars‐cov‐2 For Antiviral The...mentioning
confidence: 99%
“…The subtilisin‐like proprotein convertase, Furin, is another attractive target and its inhibitors have shown activity against multiple furin‐dependent pathogens by twofold, including Ebola virus and bird flu virus (A H5N1), via restraining viral entry and enhancing the immune response for viral clearance. 33 Furin has recently been shown to cleave the SARS‐CoV‐2 S protein, and thus Furin inhibitors could potentially be repurposed as novel drugs for COVID‐19. 297 , 298 Through structure‐based virtual screening and post‐screening biochemical assays, it was found that diminazene can effectively inhibit the activity of Furin.…”
Section: Repurposing Clinically Available Drugs and Therapies For Pat...mentioning
confidence: 99%
“…Other drugs that block ACE2 have been tested in clinical trials include bromhexine with or without hydroxychloroquine and valsartan ( NCT04355026 and NCT04335786, respectively). Furin inhibitors have been proved to inhibit viral entry and replication, and are further studied for their potential to be used as a therapeutic agent against SARS-CoV-2 ( Cheng et al, 2020 ; Devi et al, 2022 ).…”
Section: Therapeutic Targets Involving Viral Proteinsmentioning
confidence: 99%